OPTIMALISASI PEMBELAJARAN GERAK DASAR ROLL DEPAN MELALUI MODIFIKASI SARANA DAN PRASARANA PEMBELAJARAN PADA SISWA KELAS VII C SMP NEGERI 30 SEMARANG (psnppg, 2025)
This study aims to improve the learning outcomes of the Forward Roll material by modifying the learning facilities and infrastructure for Class VIIC Students of SMP Negeri 30 Semarang in the 2024/2025 academic year.This research is in the form of Classroom Action Research carried out in one cycle. In one cycle consists of two face-to-face meetings consisting of planning, implementation of actions, observation, and reflection. The research method used is a qualitative descriptive method. The subjects in this study were Class VIIC students of SMP Negeri 30 Semarang in the 2024/2025 academic year totaling 32 students consisting of 16 male students and 16 female students. Data on the results of the front roll learning were obtained through performance tests, observation sheets were used to collect data on student activities in participating in the front roll learning process through the application of modifications to learning facilities and infrastructure.
Keywords: Optimization of Learning; Forward Roll; Modification of Learning Facilities and Infrastructure.